1994
DOI: 10.7164/antibiotics.47.697
|View full text |Cite
|
Sign up to set email alerts
|

Pironetin, a novel plant growth regulator produced by Streptomyces sp. NK 10958. I. Taxonomy, production, isolation and preliminary characterization.

Abstract: A novel plant growth regulator, pironetin, was isolated from the culture broth of Streptomyces sp. NK10958.It was extracted from the culture broth with ethyl acetate and purified by column chromatographies. Pironetin showed 23% inhibition on the growth of rice plants without any loss of crop yield at lOg/a on 9 days before heading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Some of these compounds such as lactone monoalcohol (2) [6] and passifloricin A (5) [7] have been found to exhibit antifungal activity. (-)-Pironetin (6) [8] , an immunosuppressive agent, is known to inhibit cell-cycle progression in the M-phase. Kurzilactone (3) [9] and fostriecin (4) [10] are cytotoxic and anticancer agents, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these compounds such as lactone monoalcohol (2) [6] and passifloricin A (5) [7] have been found to exhibit antifungal activity. (-)-Pironetin (6) [8] , an immunosuppressive agent, is known to inhibit cell-cycle progression in the M-phase. Kurzilactone (3) [9] and fostriecin (4) [10] are cytotoxic and anticancer agents, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…pironetin (165) [299,300] and demethylpironetin (166) [301] produced potent tubulin assembly inhibition by arresting the cell cycle in M phase (G 2 /M) and showing antitumor activity against amurine tumor cell line P338 leukemia, transplanted in mice, with IC 50 value 15 µM. The antitumor activity of these compounds is due to apoptosis caused by the phosphorylation of Bcl-2 and by mitotic arrest [302] .…”
Section: Pironetin and Derivatives (165-167)mentioning
confidence: 98%
“…1) was isolated as a plant-growth regulator that induces shortening of the plant height of rice, 61,62) and as an immunosuppressor that inhibits the blastogenesis of both T and B cells. 63) In the course of investigating the molecular mechanisms, we found that pironetin showed antitumor activity against a murine tumor cell line, P388 leukaemia, transplanted in mice, and induced apoptosis via disruption of the cellular microtubule network in situ.…”
Section: Pironetinmentioning
confidence: 99%